New species and records of Goeldichironomus Fittkau, 1965 from Brazil (Diptera: Chironomidae) - Amora, Gizelle; Hamada, Neusa; Pinho, Luiz Carlos (Zootaxa, 2015)
One new species named Goeldichironomus adhaerens sp. n. is described from urban area in Manaus, Brazilian Amazon, based on male adult, pupa and larva. New records of G. neopictus Trivinho-Strixino & Strixino, G. maculatus Trivinho-Strixino & Strixino, G. pictus Reiss and G. fluctuans Reiss are also provided.